Kinetics of stone tool production among novice and expert tool makers. Issue 4 (27th October 2020) - Williams‐Hatala, Erin Marie; Hatala, Kevin G.; Key, Alastair; Dunmore, Christopher J.; Kasper, Margaret; Gordon, McKenzie; Kivell, Tracy L.
Abstract: Objectives: As is the case among many complex motor tasks that require prolonged practice before achieving expertise, aspects of the biomechanics of knapping vary according to the relative experience/skill level of the practitioner. In archaeological experiments focused on the production of Plio‐Pleistocene stone tools, these skill‐mediated biomechanical differences have bearings on experimental design, the interpretation of results, and lithic assemblage analysis. A robust body of work exists on variation in kinematic patterns across skill levels but less is known about potential kinetic differences. The current study was undertaken to better understand kinetic patterns observed across skill levels during "Oldowan, " freehand stone tool production. Materials and Methods: Manual pressure data were collected from 23 novice and 9 expert stone tool makers during the production of simple stone flakes using direct hard hammer percussion. Results: Results show that expert tool makers experienced significantly lower cumulative pressure magnitudes and pressure–time integral magnitudes compared with novices. In expert knappers, digits I and II experienced similarly high pressures (both peak pressure and pressure–time integrals) and low variability in pressure relative to digits III–V. Novices, in contrast, tended to hold hammerstones such that pressure patterns were similar across digits II–V, and they showed low variability on digit I only. Discussion: The similar and consistent emphasis of the thumb by both skill groups indicates the importance of this digit in stabilizing the hammerstone. The emphasis placed on digit II is exclusive to expert knappers, and so this digit may offer osteological signals diagnostic of habitual expert tool production.